Energy and Sun Sustainable Energy Solutions for Future Megacities - Ahati, Jiarheng; Annegarn, Harold J.; Baur, Frank; Born, Lukas; Braun, Nina; Busch, Mirjam; Derreza-Greeven, Cassandra; Detzel, Andreas; Dobbins, Audrey; Eltrop, Ludger; Eltrop, Ludger; Erhorn, Hans; et al. (JOVIS Verlag GmbH, 2014)
Solar energy is in focus worldwide. So is the role of cities and public governments for creating a more sustainable urban future. This volume highlights the role of solar energy and other solar related energy technologies for a low carbon and sustainable energy system, particularly for cities and city regions in the South. The articles refer to solar energy generation technologies, smart city planning concepts, as well as ,passive' solar building design approaches. Thus, the volume takes a broad and applied approach by analysing projects and different solutions for a more efficient and solar oriented building design and technology implementation
Description based on online resource; title from PDF title page (publisher's Web site, viewed 24. Mrz 2021)
Keywords: Archtektur; ARCHITECTURE / Urban & Land Use Planning; Energieversorgung; Solartechnik; Megastadt; Stadtplanung; Stadtentwicklung; Verstädterung; Bevölkerungswachstum; Stadt; Nachhaltigkeit; Aufsatzsammlung